The Entanglement of the Disciplines: Why an Afrocentric Methodology to Advance Humanizing Research on People of the African Diaspora. (14th October 2022) - Flannery, Ifetayo M.
Abstract : This review identifies some of the pitfalls in assuming the dominant theories, constructions of race and power, and methodological tools scholars are left to inherit in their traditional disciplinary training. In a quest for a new episteme for Black life, Africana Studies created space for methodological frameworks such as Afrocentricity. This analysis offers examples through an Afrocentric methodology to confront and repair research on Black populations that assume othering, permanent dislocation from power, land, and authority- particular to Africans in diaspora, and methodological constraints around language and conceptual construction in research on Black life. An Afrocentric methodology can and should be advanced beyond scholarship proliferating within Africana Studies. Research considerations and questions that distinguish disciplinary method from methodology are discussed. Additionally, a new conceptual framing is offered here — cultural location, as a theoretical tool for historical and cultural examinations of African diasporic groups that applies the aforementioned reorientation toward humanizing research.